Computer Tomographic Illustration of the Development of the Pulmonary Function in Bovine Neonates until the Twenty-First Day Postnatum - Bernd Linke; H. Bostedt; A. Richter (Veterinary Medicine International)
The aim of this study was to analyze the development of the lung in newborn calves. The sample consisted of 28 Holstein Friesians calves which were examined clinically, and their chest segment was measured with computed tomography. The tests were performed on the first, sixth, and twelfth hours of life and after the first, second, and third weeks. Also, blood gases and blood counts were determined. Besides Kolmogorov-Smirnov tests, analyses of variance, t-tests (on a significance level of ), and correlation analyses were used. The most significant changes occurred between birth and the first hour. However, there were significant differences in the gas filling between cranial and caudal and between dorsal and ventral parenchyma segments. This difference remained over the entire study period. At the end of the first week between 85 and 93% were involved in gas exchange. Only after the completion of the second week of life, the air supply was achieved throughout the whole lung. The pO2, pCO2, and pH values confirmed this. This study shows that a healthy bovine neonate needs about 2 weeks before all lung units are integrated into the gas exchange. This explains why calves in unfavorable environments often suffer from pulmonary affections.